BRAINIAC: The Planning Process for the E-Learning Platform with Text Summarisation Tools - Siti Nur Fatehah Nordin; Nurdiana Azizan; Noraizah Abu Bakar; Dini Onasis (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Voume 11 Issue 1 Page (122–131)